Energy Provision and Economic Growth in Emerging Economy - South Africa - Ngwakwe, Collins C. (International Journal of Energy Economics and Policy, 2020)
This paper presents an empirical analysis of public energy access imperative on economic growth in South Africa. The paper is motivated by current paucity of research regarding rural energy provision and economic growth in South Africa. Hence, this research adds a nuanced contribution to the literature by examining the relationship between rural and urban energy provision and economic growth in South Africa. Time series data on public electricity provision for South Africa were collected from 1998 to 2017 from the World Bank economic indicators’ data archive. After testing for unit root, a cointegration regression was conducted. Results from the statistical analysis indicate a cointegration relationship between urban and rural energy provision and economic growth in South Africa. This relationship is positive and significant – indicating that increased energy access for urban and rural dwellers is a veritable tool for stimulating economic growth. The paper’s finding is germane for public policy makers in charge of public energy provision. The paper highlights the need for improved public energy provision to rural communities. Further research is needed to examine the role of rural energy provision on the growth of informal economy in South Africa. Keywords: Public energy provision; economic growth; urban energy access; rural energy access; South Africa; energy provision JEL Classifications: O1; O2; H4 DOI: https://doi.org/10.32479/ijeep.9388